Pengaruh Faktor Meteorologi Terhadap Konsentrasi NO2 di Udara Ambien (Studi Kasus Bundaran Hotel Indonesia DKI Jakarta) - Yega Serlina (Fakultas Teknik, 2020)
A combustion process in power plants, industry and transportation can cause air pollution problems, one of which is the pollutant of Nitrogen Dioxide (NO2) gas. One of the stages of air quality management is monitoring. In monitoring air quality, there are several factors that need to be considered because they can affect the measurement, there are meteorological factors. This study analyzes how temperature, humidity, rainfall and wind speed affect the measured NO2 concentration. NO2 and meteorological concentration data were taken at the same time at the location of the DKI-1 air quality monitoring station (Bundaran Hotel Indonesia, DKI Jakarta). Analysis of the relationship between measured NO2 concentrations with temperature, humidity, rainfall and wind speed was performed using multiple linear regression analysis. The analysis showed that there was a strong relationship between NO2 concentration and four meteorological factors. The R2 value indicates the effect of the four meteorological factors on NO2 concentrations is 38.3% and the remaining 61.7% is influenced by other factors not included in the measurements in this study.